The relationship between integrity and job performance at Tenaga Nasional Berhad (TNB) Banda Kaba Melaka / Siti Amirah Hasan - Hasan, Siti Amirah (2019)
This study was carried out to study the relationship between integrity and job performance among employees in Tenaga Nasional Berhad (TNB) Banda Kaba Melaka. It was based on two objectives namely; (a) to study the relationship between productivity, trust, and work ethics towards job performance among the employee at Tenaga Nasional Berhad (TNB) Banda Kaba Melaka, (b) to study the most contributing variable that influence job performance among the employee at Tenaga Nasional Berhad (TNB) Banda Kaba Melaka. The study involved 123 employees of 5 departments in TNB through stratified sampling technique. To achieve the objectives, data were collected through a questionnaire that provided various dimensions of job performance. The data analysis showed that productivity, trust, and work ethic had significant positive effect on job performance. The findings of this study may help organization to enhance its integrity and its effect on job performance. Limitations and recommendations were also discussed